2020
DOI: 10.1093/dnares/dsaa027
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of tetraploid sweet basil, Ocimum basilicum L., provides tools for advanced genome editing and molecular breeding

Abstract: Sweet basil, Ocimum basilicum L., is a well-known culinary herb grown worldwide, but its uses go beyond the kitchen to traditional medicine, cosmetics and gardening. To date, the lack of an available reference genome has limited the utilization of advanced molecular breeding methods. We present a draft version of the sweet basil genome of the cultivar ‘Perrie’, a fresh-cut Genovese-type basil. Genome sequencing showed basil to be a tetraploid organism with a genome size of 2.13 Gbp, assembled in 12,212 scaffol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…About 65% of the expressed ObANS RNA encoded mutant alleles. We have also observed an expression of mutated genes in the phenylpropenes biosynthesis pathway (Gonda et al, 2020). Phenotypically, polyploids can “allow” themselves to express mutated genes more than diploids since they have gene redundancy, as in the case of the flower color of ‘Cardinal’.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…About 65% of the expressed ObANS RNA encoded mutant alleles. We have also observed an expression of mutated genes in the phenylpropenes biosynthesis pathway (Gonda et al, 2020). Phenotypically, polyploids can “allow” themselves to express mutated genes more than diploids since they have gene redundancy, as in the case of the flower color of ‘Cardinal’.…”
Section: Discussionmentioning
confidence: 87%
“…LGs were set, and map distances were calculated based on the grouping tree with the regression mapping function. Homeologous LGs were determined considering the BUSCO analysis of Gonda et al . (2020) that defined homeologous scaffolds.…”
Section: Methodsmentioning
confidence: 99%
“…Raw RNA-seq reads were filtered and cleaned using Trimmomatic (BOLGER et al 2014) to remove adapters and low-quality reads. Clean reads were mapped with STAR (DOBIN et al 2013) to the sweet basil genome (GONDA et al 2020). Transcript quantification and differential gene expression analysis were performed using Cufflinks (v2.2.1) software (ROBERTS et al 2011) combined with gene annotations.…”
Section: Basil Transcriptome Analysismentioning
confidence: 99%
“…Analysis of the genomic locations of these genes found that two pairs of the five genes are located in homeologous scaffolds based on common BUSCO (Benchmarking Universal Single-Copy Orthologs) genes (Supplementary File 6) analyzed by (GONDA et al 2020). However, XLOC_035244 possibly contains a point mutation, which results in a protein that is 79 amino acids shorter than XLOC_006768 at the C-terminus (Table 2).…”
Section: G I Have and Have Enetic Response Of Basil To P Belbahriimentioning
confidence: 99%
See 1 more Smart Citation